Odpowiedzi

2010-02-26T17:34:34+01:00
A) 5x + 2 = 7 - 3x
5x+3x = 7 -2
2x=5
x=2,5

b) -7(x - 2) = 3x - 1
-7x + 14 = 3x - 1
-7x - 3x = -1 - 14
-10x = -15 /:10
x= 1,5
c) 4(x - 1) = 6(1 + x)
4x - 4 = 6 +6x
4x-6x=6 + 4
2x = 10
x= 5
2 3 2
2010-02-26T17:38:29+01:00
5x+2=7-3x
5x-3x=7-2
2x=5
x=2,5

-7(x-2)=3x-1
-7x+14=3x-1
-7x-3x=-1-14
-10x=-15
x=1,5

4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=6+4
-2x=10
x=-5
2010-02-26T17:38:52+01:00
5x+2=7 - 3x
5x + 3x = -2 +7
8x = 5
x= 5/8

-7(x-2)=3x-1
-14x +14=3x-1
-14x-3x=-14-1
-11x=-13
x=1 2/11

4(x-1)=6(1+x)
4x-4=6+6x
-2x=10
x=-5
1 5 1